Para lang kuya a vehicle route mapping mobile application for jeepney commuters in Cebu - Sanjorjo, Angelyn M. (2014)
This study provides a solution to the current routing problem within the road network in cities. The study presents the creation of a mobile application that will serve as a route guide within Cebu premises. This application makes use of the current active jeepney routes within the city. The main problem solved by this study is to provide the user a sequential list of jeepney rides one should take given a source and destination point. The shortest path sequence incurs the shortest distance traveled within the graphical road network representation of the city. The solution for this shortest path problem was solved through Dijkstra?s algorithm. The shortest distance was retrieved through the process of traversing every edge within the final list of path. Road distances between these points were retrieved through a JSON request to the Google Maps service, which also then helps in graphically representing/drawing the road path in the embedded Google Maps within the application. Also, it provides the user the estimated time travel with regards to traffic ? heavy, moderate and light. The application is developed under the Android platform and through the Native Google Maps API ? a mobile platform development provided by Google Maps. Tests were also conducted to test efficiency and accuracy of the application upon solving the problem. Results show that the application got high accuracy rate, by approximately 96%. Currently, the application supports 16 routes out of approximately 50 active routes within the city. This developed application is only limited to the main roads in Cebu City. Although this application does not yet include all the jeepney routes available in the city, it shows a good start for a newly developed application that could solve routing problems involving shortest path solutions.